PENGARUH TEKNIK AUDIT BERBANTUAN KOMPUTER, PELATIHAN PROFESIONAL, DAN ETIKA PROFESI TERHADAP KINERJA AUDITOR - Pratiyaksa, I Gusti Agung Made Wira; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2016)
The development of technology in today's times, leading information technology will continue to evolve subsequently affects every stage of the audit process. Auditors are expected to apply Computer Assisted Audit Techniques as one influence on the development of IT and to improve its performance. This study aims to determine the effect TABK, professional training, and professional ethics on the performance of auditors in the KAP of the province Bali. The data collection is done by distributing questionnaires to the auditor in public accounting firms that are members of the Indonesian Institute of Accountants (Certified) Bali region as respondents using purposive sampling technique sampling. The analysis technique used is multiple linear regression. Based on the results obtained show that TABK, professional training and professional ethics have positive influence on the performance of auditors. This shows that the increasing use of TABK and auditors who often follow professional training as well as the auditor who abide by the ethics of the profession, the auditor's performance is increasing.
Keywords: Performance Auditor, Computer Assisted Audit Techniques, Professional Training, Professional Ethics